1986
DOI: 10.1139/b86-110
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interactions of ectomycorrhizal mycobionts under field conditions

Abstract: A rapid field method to evaluate the competitive performance of selected ectomycorrhizal isolates is presented. Ectomycorrhizal jack pine seedlings and noninoculated controls produced in growth pouches were outplanted in diverse stations 1 month after inoculation. Photographs taken prior to outplanting and at the time of excavation permitted comparative observations of mycorrhizal development along each lateral root of individual seedlings. Nonmycorrhizal control seedlings showed 0, 20, 20, and 76% mycorrhizal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 0 publications
1
21
1
Order By: Relevance
“…Genotyping (table IV) showed that these Laccaria-like mycorrhizas or undetermined mycorrhizas were mainly formed by a new ribotype (ribotype 1/3) coming from the plantation site. Its ITS rDNA pattern was different from the several hundreds patterns recorded in the INRA MycoMol database or in other ITS databases [15,20].…”
Section: Survival and Effect Of Laccaria Bicolor S238n On Douglas Fircontrasting
confidence: 83%
See 1 more Smart Citation
“…Genotyping (table IV) showed that these Laccaria-like mycorrhizas or undetermined mycorrhizas were mainly formed by a new ribotype (ribotype 1/3) coming from the plantation site. Its ITS rDNA pattern was different from the several hundreds patterns recorded in the INRA MycoMol database or in other ITS databases [15,20].…”
Section: Survival and Effect Of Laccaria Bicolor S238n On Douglas Fircontrasting
confidence: 83%
“…Despite the imprecision of such methods, some results are available in the litterature. McAfee and Fortin [20] observed on Pinus banksiana seedlings that the inoculated fungus, Laccaria bicolor, colonised 55% of the short roots after two months in the field. Danielson and Visser [7] found that Laccaria proxima and Thelephora terrestris were completely superseded by naturally occurring fungi one year after transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Intraspecific genetic variation shown in this study could be used to screen genetically difFerent isolates before use in mycorrhizal trials. Indeed, genetic differences might reflect intraspecific variations in ectomycorrhizal aggressivity (Perry, Molina & Amaranthus, 1987;Sen, 1990fl, b;' VV' ong & Fortin, 1990;Albrecht, Burgess & Lapeyrie, 1994;Rosado, Kropp & Piche, 1994), the ability to improve mineral nutrition and growth of young host trees (Harley & Smith, 1983;Le Tacon, 1985;Harley, 1989;Lamhamedi et a/., 1990;Sen, \990b), the protection of root systems against phytopathogenic fungi (Marx, 1969;Marx, 1972;Perrin, 1985) and ability to compete with other ectomycorrhizal symbionts (McAfee & Fortin, 1986). This work shows that isozyme analysis combined with somatic incompatibility testing are efficient tools with which to study the population biology of ectomycorrhizal fungi found under forest trees.…”
Section: Discussionmentioning
confidence: 99%
“…in the outplanted soil, while other species are quite competitive and persist for years (Lamb, 1979;Fleming, 1985;McAfee & Fortin, 1986;Villeneuve et al, 1991;Selosse et al, 1998;Wu et al, 1999). Persistence may be related to the ability of a species to exclude others from colonizing roots (Fleming, 1985;Mamoun & Olivier, 1993a,b;Olivier & Mamoun, 1994).…”
Section: Tablementioning
confidence: 99%